The Effect of Perceived Ease of Use and Perceived Usefulness on Mobile Payment Usage - Pratiwi, Mirna Tria (Lembaga Penerbitan Unversitas Esa Unggul, 2019)
This study aims to find out how to increase intention to use LinkAja in Semarang by testing a TAM model that integrates the role of perceived ease of use and perceived usefulness into the intention to use LinkAja. Extant research from various research stream is reviewed, resulting in 4 hypotheses. Data collected from 100 LinkAja users in Semarang are examined through path analysis model and processed by SPSS Statistics 23.Based on the results of hypotheses testing, there are 3 accepted hypotheses and 1 rejected hypothesis. The results show that perceived ease of use has significant and positive effect on perceived usefulness, perceived usefulness has significant and positive effect on intention to use LinkAja, perceived ease of use has significant positive effect on intention to use LinkAja. To increase the intention to use LinkAja can be done by increasing perceived ease of use LinkAja.Keywords: Perceived ease of use, Perceived usefulness, Intention to use